Effects of some environmental stresses on nutrients concentration of Phragmites australis and use it as fodder - Muthik Abd Muslim Guda (Al-Qadisiyah Journal of Veterinary Medicine Sciences, 2018)
This study has been conducted to assess and analyze the nature and environmental characteristics of Baher Al-Najaf depression (BAND) and their effect on nutrients Concentration of Phragmites australis as responses to Environmental Stresses and use it as fodder, has been studied for 12 months in four different sites. Samples were collected monthly for the period February 2015 to January 2016, taken from four selected sites in (BAND), Iraq. The environmental factors of water studied include: Temperature, Electrical Conductivity (EC), Salinity, Water pH, Total Dissolved Solids (TDS), Turbidity, Total Suspended Solids (TSS), Dissolved Oxygen (DO), Total Hardness (TH), ions, Total Nitrogen (TN), Total Phosphorus (TP), Bicarbonate (HCO32-), Sulfate (SO42-), Chloride (Cl-1), and sodium (Na1+) ions. Results of water quality have proved the highest values of environmental factors were in autumn and summer while the least environmental factors were in winter and spring. Environmental factors were gradients significantly high at site as follows S2 > S3 > S4 > S1.The studied factors of climate are Air Temperature, Relative Humidity, Intensity of Solar Radiation, Precipitation Rates, Day Length and Evaporation Rate. Results have shown that climatic factors affected water resources and salinity level in (BAND). The changes in the nutrient cycling and/or accumulation are in most cases unpredictable, and that is why a detailed description of the local structure and state of within-stand development are necessary. The ability and translocation are important, especially in changing environments with a varying supply of resources. Ionic contents Na+ and Cl- significantly increased, whereas K+, TP (Total Phosphor) and TN (Total Nitrogen) decreased with increasing levels of environmental stresses in each site and season. In general, it can be used Phragmites australis as fodder in suitable environmental factors and it cannot be used as fodder in stress environmental factors due to decrease in nutrients concentration of Phragmites australis.